Kesadaran Hukum Santri Salafiyah Safiiyah Sukorejo Situbondo Terhadap Peraturan Pesantren - Fathorrahman Fathorrahman (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Abstract. This research aims to explore legal awareness and students' acceptance of various existing Islamic boarding school regulations. Awareness is a pattern of assessment of existing Islamic boarding school laws or regulations, including the regulations desired by all students as one of the actors in these regulations. With high legal awareness, the level of student violations should decrease. In this research, the sample data that will be used is a number of students who are registered or have been registered on the list of student offenders and several students who have never or have a very low level of violation. Then, the type of research used in this case is qualitative descriptive research. The theory used is the theory of legal consciousness, legal system and collective consciousness.